2016
DOI: 10.1111/ecc.12521
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychological distress in advanced cancer patients under palliative treatments

Abstract: This work aims to investigate the factors associated with psychological distress in advanced cancer patients under palliative treatment. We comprehensively assessed the demographic, psychosocial and health factors of 158 advanced cancer patients. Patients with high and low distress, according to the Hospital Anxiety and Depression Scale, were compared. A regression analysis was built to identify the best predictors of distress. Patients with high psychological distress (81%) were more likely to have lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 69 publications
1
44
0
7
Order By: Relevance
“…Many patients with advanced cancer experience negative moods, including anxiety, depression, stress, and fear, in anticipation of potential cancer‐related complications or death . There is a growing recognition that negative emotions can increase pain, weakness, and hopelessness; can even lead to suicide; can increase medical costs; and can disrupt patients' quality of life and therapeutic success . Therefore, health policies in many countries throughout the last decade have prioritized detecting and addressing the psychological needs associated with cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Many patients with advanced cancer experience negative moods, including anxiety, depression, stress, and fear, in anticipation of potential cancer‐related complications or death . There is a growing recognition that negative emotions can increase pain, weakness, and hopelessness; can even lead to suicide; can increase medical costs; and can disrupt patients' quality of life and therapeutic success . Therefore, health policies in many countries throughout the last decade have prioritized detecting and addressing the psychological needs associated with cancer .…”
Section: Introductionmentioning
confidence: 99%
“…The PT patients in this study were generally considered to be persistently depressed preoperatively through postoperative month 6. In particular, patients who received a postoperative histological diagnosis of malignancy were highly depressed; this finding possibly reflected concerns over the diagnosis, in the same way as has been reported for patients with other cancers [ 10 , 29 , 30 ]. PC has a poor prognosis, and survival rates are poor even when operable [ 1 ].…”
Section: Discussionmentioning
confidence: 56%
“…10 High levels of hopelessness, emotional instability and distortion of self-image are associated with high psychological distress in patients with advanced cancer. 11 Psychological symptoms may infl uence physical symptoms. A study of the relationship between depression and the burden of physical symptoms in cancer found that depression was signifi cantly related to the number and severity of physical symptoms.…”
Section: Needs Assessmentmentioning
confidence: 99%